2003
DOI: 10.1107/s0021889803008422
|View full text |Cite
|
Sign up to set email alerts
|

Polymer hydration and microphase decomposition in poly(N-vinylcaprolactam)–water complex

Abstract: Poly(N‐vinylcaprolactam) (PVCL) is a synthetic analogue of biomolecules (enzymes, proteins). It demonstrates a specific hydration and undergoes a coil–globule transition. The PVCL–D2O system (PVCL mass M = 106) has been investigated by small‐angle neutron scattering (SANS) at T = 296–316 K to identify the structural features of the collapse at concentration C = 0.5 wt% near the threshold of the coil overlap. (The collapse leads to the segregation of the phase enriched with polymer at T > 305 K). The SANS exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…To investigate this, an extremely dilute solution is needed of high molar mass samples to avoid the strong tendency to aggregate (concentration lower than 1 g/L). The observation of the coil to globule transition in water for PNVCL with a molar mass M w ~1 000 000 g/mol, was reported by light scattering techniques [5] and in deuterated water by small angle neutron scattering [37]. Indirectly it has previously been observed that an increase of solution temperature from 10 °C to 30 °C is accompanied by an approximately two-fold reduction in intrinsic viscosity of PNVCL in water; this was explained by the shrinkage of polymer coils accompanied by partial dehydration [22].…”
Section: Poly(n-vinylcaprolactam) (Pnvcl)mentioning
confidence: 90%
“…To investigate this, an extremely dilute solution is needed of high molar mass samples to avoid the strong tendency to aggregate (concentration lower than 1 g/L). The observation of the coil to globule transition in water for PNVCL with a molar mass M w ~1 000 000 g/mol, was reported by light scattering techniques [5] and in deuterated water by small angle neutron scattering [37]. Indirectly it has previously been observed that an increase of solution temperature from 10 °C to 30 °C is accompanied by an approximately two-fold reduction in intrinsic viscosity of PNVCL in water; this was explained by the shrinkage of polymer coils accompanied by partial dehydration [22].…”
Section: Poly(n-vinylcaprolactam) (Pnvcl)mentioning
confidence: 90%
“…The overview of R g values as obtained for all PNIPMAm/PNIPAm samples under SANS investigation is presented in Table 2; R g values obtained for PVCL/ PNIPAm hydrogels are shown in Table 3. Similar sizes of globular structures at temperatures above the phase transition as shown in Tables 2 and 3 for PNIPMAm/PNIPAm and PVCL/PNIPAm IPN hydrogels by SANS and small-angle X -r a y s c a t t e r i n g w e r e a l s o r e p o r t e d f o r o t h e r thermoresponsive systems, e.g., for PVCL and poly(N,Ndiethylacrylamide) aqueous solutions and gels [19,41,45]. For all the PNIPMAm/PNIPAm IPN samples, we have observed approximately same sizes at each temperature.…”
Section: Characterization Of Ipn Hydrogel Samplesmentioning
confidence: 99%
“…2131 Moreover, in contrast to PNIPAM, PVCL possesses a “classical” Flory–Huggins thermoresponsive phase diagram. 32,33 Indeed, PVCL has a continuous coil-to-globule phase transition behavior with the LCST ranging from 32–50°C, which depends on PVCL molecular weight and concentration. 34,35 This unique feature affords controlling temperature sensitivity of the polymer by varying its molecular weight.…”
Section: Introductionmentioning
confidence: 99%